Monitoring of fruit fly in mandarin orchards of Jajarkot, Nepal: A mixed-method approach - Parajuli, Arpan; Timilsina, Ram Hari; Paudel, Bibechana; Karki, Nabina; Upadhya, Krishna Prasad; Basnet, Pitamber; Adhikari, Debraj (Fundamental and Applied Agriculture, 2023)
The study was conducted to access the species diversity of fruit fly and their population dynamics, awareness among mandarin growers on the nature of damage, and factors affecting the awareness in the Jajarkot district of Nepal in 2021. The study consists of two parts: farmer’s survey and monitoring of fruit flies. The farmer’s survey was carried out in randomly selected sixty households whose orchards were at least five years old in command areas of citrus zone, Jajarkot. Fruit fly monitoring was done in three mandarin orchards of Kushe Rural Municipality and Bheri Municipality using cuelure, methyl eugenol, and great fruit fly bait. The survey revealed that only thirty percent of the farmers were aware of the nature of fruit fly damage. Experience in mandarin cultivation was found to be significantly affecting the awareness of mandarin growers on fruit fly damage. The mandarin growers were practicing pruning, collection and destruction of fallen fruits, use of chemicals, and traps for fruit fly management. Monitoring data revealed that there were four major fruit fly species. Among the lures used, cue-lure attracted more number of fruit flies, followed by methyl eugenol and great fruit fly bait. Cue-lure trap was effective in trapping Bactrocera nigrofemoralis, Zeugodacus tau, and Zeugodacus scutellaris whereas methyl eugenol was found effective in trapping Bactrocera dorsalis. Great fruit fly bait captured Bactrocera nigrofemoralis and Zeugodacus tau, but in lesser number. The number of all the species of fruit fly started increasing in April and reached the highest during May.